Higher Education Governance - International Experience and Lessons for Vietnam - Hai, Pham Thi Thanh; Giang, Nguyen Thi Huong; Anh, Vu Thi Mai; Quang, Hoang Ngoc (VNU Journal of Science: Education Research; Vol 35 No 3DO - 10.25073/2588-1159/vnuer.4282, 2019)
Higher education Governance refers to the legality of decision-making in universities between different governance structures (faculty, scientific council and university council) and the organizational structure (administrative structures). (Subjects, training programs, rector and vice rectors). The purpose of higher education Governance is to clarify common interests and identify their goals while defining the limits of authority in reasoning and practice - who will decide and the focus of the decision. Using comparative educational research methods, this paper analyzes the issue of university governance in the United States and Israel, from which a number of recommendations are proposed for Vietnam's higher education Governance for the ministry and role responsibility of the university council and the rector of higher education institutions.